The transformative potential of a vulnerability focus in basic assistance policies : a study on UNHCR and IOM in Sudan - Flegar, Veronika Lydia Birgit, 1989- (Cambridge : Intersentia, 2020)
The term 'vulnerability' is often used in law and policy to refer to disadvantaged, marginalized or excluded human beings. This book explores how a vulnerability focus in basic assistance policies can contribute to substantive equality and therefore to the realization of universal human rights in the migration context. It concentrates on the potential that such a vulnerability focus can have to mitigate stigmatization and stereotyping and to facilitate socio-economic participation.
Title from publisher's bibliographic system (viewed on 11 Nov 2021).
English text with Dutch summary.
Keywords: Humanitarian assistance -- Sudan; Marginality, Social -- Sudan; Human rights -- Sudan; United Nations. -- Commission on Human Rights; International Organization for Migration